Effects of the COVID-19 Pandemic on Psychological Well-Being and Mental Health Based on a German Online Survey - Lingelbach, Katharina; Piechnik, Daniela; Gado, Sabrina; Janssen, Doris; Eichler, Martin; Hentschel, Leopold; Knopf, Dennis; Schuler, Markus; Sernatinger, Daniel; Peissner, Matthias (Frontiers in Public Health, 2021)
Objective and Background: To contain the COVID-19 pandemic, public health actions have changed the everyday life with an inevitable impact on individuals and their social life. Since intact (socio-)psychological functioning and mental health are protective factors contributing to the immune system and preventing diseases, it is crucial to identify individuals with increased vulnerability. Method: We conducted a German online survey from April until August 2020 investigating health-related, social, behavioral, and psychological effects of the COVID-19 pandemic. 173 adults participating in the survey were analyzed (39.9 % male, age: M = 44.81 +/- 13.31). We explored effects on mental health by (a) clustering participants in two clusters and (b) analyzing the clusters using correlations and regression models. Results: Participants belonged either to a cluster characterized by higher general well-being or to a more concerned cluster depending on their responses. The correlation analysis revealed a significant negative relation between age and well-being with younger participants revealing higher depression scores in the concerned cluster. Furthermore, multiple regression models revealed that the number of risk factors only has a significant influence on psychological well-being in the concerned but not in the comfortable cluster. Conclusion: We found that especially participants at (a) younger age and (b) greater risk of a severe course of disease reported reduced mental well-being and seemed to be weakened in their psychological protective factors in our sample. These insights allow to provide tailored recommendations for preventive and immediate actions to promote psychological well-being and reduce stress.